Imagining Infidelity: Gender Differences in Episodic Future Thinking - Karaca, Gizem (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
Current research concentrated on gender differences in terms of the episodic future thinking by including infidelity which is a stressful experience, as a manipulator. In detail, current study focused on the question of how episodic future thinking of people would be affected when they were asked to imagine being cheated, and whether this effect would differ in terms of gender. Two facets of the episodic future thinking were analysed in detail; centrality of the event and phenomenological characteristics. There was insignificant difference in terms of infidelity between the ratings of male and female participants and no significant difference in answers to both sexual and emotional infidelity in CES results. This was also revealed that it was insignificant interaction between gender and two form of infidelity. We expected that women’s score would be higher than men for both types of infidelities, but only for visual imagery, spatial imagery, and perspective significant differences were found among two groups. Moreover, results did not demonstrate a significant difference between sexual infidelity and emotional infidelity in terms of AMQ, plus insignificant interaction effect was found for gender and infidelity types on AMQ. In conclusion, current study revealed insignificant difference between men and women in terms of episodic future thinking. Keywords: Infidelity, CES, AMQ, Gender, Episodic Future Thinking

ÖZ: Bu araştırmada, stresli bir deneyim olan aldatma manipülatör olarak çalışmaya dâhil edilip, katılımcıların epizodik gelecek düşünceleri açısından cinsiyet farklılıklarına odaklanılmıştır. Detaylı olarak bu çalışma, insanların aldatıldıklarını hayal ettiklerinde, epizodik gelecek düşüncelerinin nasıl etkileneceği ve bu etkinin cinsiyetler arasında farklı olup olmadığı sorusuna odaklanmıştır. Epizodik gelecek düşüncesinin iki yönü ayrıntılı olarak değerlendirilmiştir; olayın merkeziliği ve fenomonolojik özellikleri. Erkek ve kadın derecelendirmeleri arasında aldatma açısından anlamlı bir fark olmadığı ve CES sonuçlarında cinsel aldatma ve duygusal aldatmaya tepkilerde anlamlı bir fark olmadığı sonucuna varılmıştır. Ayrıca, cinsiyet ve aldatma türü arasında anlamlı bir etkileşim olmadığı bulunmuştur. Buna ek olarak, kadınların her iki tür aldatma için erkeklerden daha fazla puan alacağının varsayıldığı bu çalışmada, sonuçlar, iki grup arasındaki farklılığın yalnızca görsel imgeleme, mekânsal imgeleme ve perspektif için anlamlı olduğunu göstermiştir. Sonuçlar, cinsel aldatma ve duygusal aldatma arasında, AMQ açısından, anlamlı bir fark olmadığını ayrıca cinsiyetin ve aldatma türlerinin AMQ üzerinde, etkileşim etkisinin olmadığını göstermiştir. Sonuç olarak, Bu çalışma, epizodik gelecek düşüncesi açısından erkekler ve kadınlar arasında anlamlı bir fark olmadığını ortaya koymuştur. Anahtar Kelimeler: Aldatma CES, AMQ, Cinsiyet, Epizodik Gelecek Düşüncesi
Master of Science in General Psychology. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Psychology, 2020. Supervisor: Asst. Prof. Dr. Burcu Kaya Kızılöz
Keywords: Psychology; General Psychology; Episodic memory; Infidelity; CES; AMQ; Gender; Episodic Future Thinking